2018
DOI: 10.15835/buasvmcn-asb:2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities (antioxidant and antimicrobial activity) of the aqueous extracts and essential oil of Ammoides verticillata (Nounkha)

Abstract: The phytochemical review conducted on the aerial part Ammoides verticillata has revealed the presence of six chemical families: flavonoids, tannins; gallic tannins, anthocyanins and the coumarins, cateichic tannins. The aqueous extract of the Ammoides verticillata could bring back the stable free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) to the yellow-colored diphenylpicrylhydrazine with an IC50 of 0.020 mg.mL-1. It is gifted with antioxidant activity, however it was less effective than vitamin C (0.001 mL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…These results were also in agreement with those reported by the work of Felidj et al 27 and Benaissa, 28 which confirmed the presence of tannins, flavonoids and triterpenes. These results were confirmed by the work of Mohamed Said and Benmansour 29 and Hafiane and Ounnas 30 where they recorded the presence of 06 chemical groups: flavonoids, tannins, gallic tannins, catechin tannins, anthocyanins and coumarins. It has already been noted that this plant contained a large amount of tannins.…”
Section: Qualitative Analysissupporting
confidence: 66%
“…These results were also in agreement with those reported by the work of Felidj et al 27 and Benaissa, 28 which confirmed the presence of tannins, flavonoids and triterpenes. These results were confirmed by the work of Mohamed Said and Benmansour 29 and Hafiane and Ounnas 30 where they recorded the presence of 06 chemical groups: flavonoids, tannins, gallic tannins, catechin tannins, anthocyanins and coumarins. It has already been noted that this plant contained a large amount of tannins.…”
Section: Qualitative Analysissupporting
confidence: 66%